Original paperENDURANCE EXERCISE TRAINING AND DIFERULOYL METHANE SUPPLEMENT: CHANGES IN NEUROTROPHIC FACTOR AND OXIDATIVE STRESS INDUCED BY LEAD IN RAT BRAIN - Dabidi Roshan, V.; Hosseinzadeh, S.; Mahjoub, S.; Hosseinzadeh, M.; Myers, J. (Biology of Sport, 2013)
Lead is a highly neurotoxic agent that particularly affects the developing central nervous system. In the current study we investigated the neuroprotective effects of exercise training and/or diferuloyl methane (DM) supplement, which is known as curcumin, on lead acetate-induced neurotoxicity in the rat hippocampus. Sixty rats were randomly divided into six groups: 1) lead acetate, 2) DM supplement, 3) endurance training, 4) training+ DM supplement, 5) sham and 6) base. The rats in the training groups performed treadmill running consisting of 15 to 22 m · min-1 for 25 to 64 min, 5 times a week for 8 weeks. All groups except sham received lead acetate (20 mg · kg-1), whereas the sham group received DM solvent. In addition, the DM and training+DM groups received DM solution (30 mg · kg-1) intraperitoneally. Chronic administration of lead acetate resulted in a significant increase in the malondialdehyde (MDA) in plasma, but not in the hippocampus. In addition, it led to significantly decreased brain-derived neurotrophic factor (BDNF) in the hippocampus and total antioxidant capacity (TAC) levels, as compared to the sham group. Treadmill running, DM supplementation, or both resulted in a significant decrease in MDA levels and significantly increased BDNF and TAC levels, as compared to the lead acetate group. These results provide a rationale for an inhibitory role of DM supplement and regular exercise in the attenuation of lead-induced neurotoxicity.